A new approach to stabilisation of a class of nonlinear systems with an output constraint - Chen, Chih-Chiang; Sun, Zong-Yao (International journal of control, 2020)
This paper investigates the problem of state-feedback stabilisation for a class of high-order nonlinear systems with an output constraint. A novel tangent-type barrier Lyapunov function is first developed to cope with the output constraint. Then, by introducing the sign function and incorporating the developed tangent-type barrier Lyapunov function, the celebrated adding a power integrator technique is revamped to systematically design a continuous state feedback stabilising controller that prevents violation of the output constraint during operation. The novelty of this paper is the development of an unified design procedure, which can tackle the stabilisation task of the systems with/without the output constraint simultaneously.